Multidisciplinary management of a patient with eyelid ecthyma gangrenosum due to Pseudomonas aeruginosa infection - Gallego-Amorós, Marta; Temblador Barba, Irene; Rodríguez Suárez, Alejo Honesto; Ruiz Rodríguez, Enrique; Pérez Cortés, Salvador (Indian Journal of Case Reports, 2024)
Pseudomonas aeruginosa is a Gram-negative bacillus, responsible for frequently serious infections that cause high morbidity and mortality, especially in immunosuppressed hosts or with underlying malignant processes. Ecthyma gangrenosum is a highly suggestive, though not pathognomonic, manifestation of disseminated P. aeruginosa infection. The palpebral presentation of the latter is estimated to be